2018
DOI: 10.4196/kjpp.2018.22.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Morroniside on anti-inflammation activities in rats following acute myocardial infarction

Abstract: Our previous studies have confirmed that morroniside has neuroprotective effects. However, the effects of morroniside on cardiac myocardium remain unknown. Rats were anaesthetized with 10% chloral hydrate (0.35~0.4 mL/kg) and an acute myocardial infarction (AMI) was induced by ligating the anterior descending coronary artery (LAD). Following AMI, morroniside was administered intragastrically for 3 consecutive days at doses of 45, 90 and 180 mg/kg, respectively. Lactate dehydrogenase (LDH) and cardiac troponin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Corni fructus , a component of ALWPs, has anti-inflammatory effects by suppressing COX-2 and iNOS levels through the downregulation of NF-κB binding activity in macrophages ( Sung et al, 2009 ). Morroniside is a major component of C. officinalis , a component of ALWPs, and reduces proinflammatory cytokine IL-6 and IL-1β levels in a rat model of acute myocardial infarction ( Yu et al, 2018 ). In addition, type 2 diabetic rats orally administered morroniside, a component of ALWPs, exhibit downregulated NF-κB activity in hepatic tissue ( Park et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Corni fructus , a component of ALWPs, has anti-inflammatory effects by suppressing COX-2 and iNOS levels through the downregulation of NF-κB binding activity in macrophages ( Sung et al, 2009 ). Morroniside is a major component of C. officinalis , a component of ALWPs, and reduces proinflammatory cytokine IL-6 and IL-1β levels in a rat model of acute myocardial infarction ( Yu et al, 2018 ). In addition, type 2 diabetic rats orally administered morroniside, a component of ALWPs, exhibit downregulated NF-κB activity in hepatic tissue ( Park et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Loganin had a protective effect against hepatic oxidative stress [12]. Morroniside showed effective anti-inflammatory properties in AMI rats [13]. Sweroside could ameliorate liver injury by decreasing oxidative damage and inhibiting the production of proinflammatory kinases [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that AMI can lead to necrosis and initiate chronic cardiac dysfunction and pathological cardiac remodelling [4]. Although there are advances in the treatment of AMI, the irreversible loss of cardiomyocytes still leads to left ventricular remodeling and ischemic heart failure [5]. Therefore, it is vital to identify novel therapeutic drugs for the treatment of AMI.…”
Section: Introductionmentioning
confidence: 99%